Recent trends in business financial risk: A bibliometric analysis - Ali Murad Syed; Hana Saeed Bawazir (Cogent Economics & Finance, 2021)
The finance literature is giving more attention to financial frisk aspects. However, in literature, only a fragmented comprehension is known about the contextual influence of financial risk aspects of businesses. In this article, we contribute by carving out the intersections between Finance and Risk and analyze the production as well as visualize the evolution and trends of this field. In our research approach we use bibliometric technique to analyze 10 years of publications in Web of Science (WoS) database and present a comprehensive contextual picture of financial risk research. We analyzed 3024 publications by identifying the most prominent journals, authors, articles, countries and collaboration among authors and countries. Moreover, a co-occurrence analysis between authors, keywords and journal was done along as well as cluster analysis and thematic analysis is also performed to find the evolutionary trends. Our results showed that credit risk is the most trend topic over the last 10 years and performance and risk taking are two most inter-connected words using co-occurrence citation analysis. Our analysis showed that the corporate governance, financial crisis, financial innovation, and entrepreneurship are evolving themes and their occurrence is increasing and become more prominent in the in the domain of financial risk.
Keywords: 330; co-occurrence analysis; financial crisis; Financial risk; h-index; Risk; thematic analysis; trend analysis